Self-adhesive gel as well as preparation method and application thereof in scar repair

By developing a self -adhesive gel containing a self -adhesive gel with polyethylene siliconxane, polyethylene gobohyl, sanneid, water -free and water -free, and water -free, solved the treatment of existing silicon ketonic dressing The problems of long use time, poor decoration effect, high recurrence rate, and fixed equipment needed problems, realizing the effects of shortening time, significant effects, low recurrence rate, and convenient use.

CN119345116AInactive Publication Date: 2025-01-24BEOGENE BIOTECH GUANGZHOU

Patent Information

Application Number
CN202411481172.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2025-01-24
Estimated Expiration
Not applicable · inactive patent

Smart Images

  • Figure CN119345116A_ABST
    Figure CN119345116A_ABST
Patent Text Reader

Abstract

The invention relates to a self-adhesive gel and a preparation method and application thereof in scar repair, the self-adhesive gel comprises germanene, polydimethylsiloxane, polyvinylpyrrolidone, triamcinolone acetonide, absolute ethyl alcohol and water, when the self-adhesive gel is used, ethyl alcohol and water in the self-adhesive gel can be rapidly volatilized to form a layer of self-adhesive polymer film, the self-adhesive polymer film is firmly adsorbed on the tissue surface, and the self-adhesive gel can be used for repairing scars. Meanwhile, polydimethylsiloxane can retain water, germanene has a photo-thermal effect and is beneficial to promoting diffusion and absorption of triamcinolone acetonide to tissues, and the self-adhesive gel can be used for preparing scar repair medicaments.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of medical biomaterials, in particular to a self-adhesive gel and a preparation method thereof and application thereof in scar repair. Background Art

[0002] At present, the main method for clinical treatment of hypertrophic scars is surgical excision. Surgery is the fastest and most effective way to remove scars and restore relatively smooth skin. Small scars are often completely removed by intralesional nucleotomy. In addition to simple excision, medium and large scars should also be supplemented with a combined surgical method of skin graft or flap repair. However, the recurrence rate of scar hyperplasia using surgical excision alone is as high as 45-100%. After all, surgery itself is also a kind of trauma. Due to its high recurrence rate, simple surgical excision is rarely used in clinical practice to treat scar hyperplasia. After surgery, other auxiliary treatment methods are generally selected to prevent the recurrence of keloids.

[0003] Since 1983, silicone dressings have been used to treat hypertrophic scars and keloids and are considered safe and effective, gradually improving scar color, size, erythema, flexibility, pain, and itching. Its mechanism of action is due to the hydration of the corneal layer of the skin, regulating the cell signaling between fibroblasts and keratinocytes mediated by cytokines. Silicone can retain water on the surface of the scar, playing a role similar to the stratum corneum of the skin, reducing the exchange of water with the external environment, inhibiting the proliferation of capillaries and the deposition of collagen. In addition, silicone dressings increase the water content of the stratum corneum of the skin, and hydration occurs. The mechanism is that the water-soluble proteins and low-molecular-weight water-soluble inflammatory mixtures in the scar diffuse to the body surface, reducing the water-soluble products in the matrix, reducing the fluid pressure, and softening the scar body.

[0004] Although silicone dressings are widely used in clinical practice, they still have some disadvantages: 1. They need to be used repeatedly for a long time, usually 3-6 months. 2. Currently, silicone dressings have poor scar fading effects and are prone to recurrence. 3. When using silicone dressings, they must be fixed with bandages or elastic pressure bands to make them tightly combined with scar tissue. These disadvantages will lead to poor patient compliance and easily limit the clinical promotion of the product.

[0005] Therefore, there is an urgent need to develop new scar dressings. Summary of the invention

[0006] In view of the above problems, the present invention provides a self-adhesive gel and a preparation method thereof, and the obtained gel can be used for scar repair.

[0007] One aspect of the present invention provides a self-adhesive gel, the raw materials of which include germanium, polydimethylsiloxane, polyvinyl pyrrolidone, triamcinolone acetonide, anhydrous ethanol and water.

[0008] The gel system uses anhydrous ethanol and water as solvents, polydimethylsiloxane and polyvinylpyrrolidone as the main film-forming substances, and loads germanene and polydimethylsiloxane at the same time. When used, the ethanol and water therein will evaporate quickly to form a self-adhesive polymer film, which is firmly adsorbed on the tissue surface, does not require additional bandages or elastic bands for fixation, and is convenient to use. At the same time, polydimethylsiloxane can retain moisture, play a role similar to the stratum corneum of the skin, reduce the exchange of water with the external environment, inhibit the proliferation of capillaries and the deposition of collagen, and can play a role in hydrating and softening scars. Germanene has a photothermal effect and can respond to the 1064nm laser self-heating and heating. Appropriate high temperature can expand capillaries and collagen tissues and increase permeability. On the one hand, it is conducive to the penetration of water vapor into tissues and enhances the hydration and softening effect on scar tissues; on the other hand, appropriate high temperature and high permeability are conducive to promoting the diffusion and absorption of triamcinolone acetonide into scar tissues and enhancing the therapeutic effect of triamcinolone acetonide.

[0009] Preferably, in terms of weight percentage, it contains germanium: 1% to 3%, polyvinylpyrrolidone: 10% to 20%, polydimethylsiloxane: 5% to 15%, triamcinolone acetonide: 1% to 5%, anhydrous ethanol: 30% to 50%, and water: 20% to 40%.

[0010] More preferably, in terms of mass ratio, polyvinyl pyrrolidone: polydimethylsiloxane = 0.7-3:1, the gel system is stable and has good film-forming properties. More preferably, polyvinyl pyrrolidone: polydimethylsiloxane = 1.5:1.

[0011] More preferably, in terms of mass ratio, polyvinyl pyrrolidone: water = 1: 1-4, polydimethylsiloxane: anhydrous ethanol = 1: 3-7, the film-forming property is better. More preferably, polyvinyl pyrrolidone: water = 1: 2, polydimethylsiloxane: anhydrous ethanol = 1: 4.

[0012] More preferably, according to weight percentage, it contains germanene: 2%, polyvinylpyrrolidone: 15%, polydimethylsiloxane: 10%, triamcinolone acetonide: 3%, anhydrous ethanol: 40%, and purified water: 30%.

[0013] The present invention also provides a method for preparing the self-adhesive gel, comprising the following steps: (1) mixing and evenly dispersing a formulated amount of water, germanium, triamcinolone acetonide and polyvinylpyrrolidone to obtain a jelly; (2) adding a formulated amount of anhydrous ethanol and polydimethylsiloxane to the jelly obtained in step (1), and continuing to mix and evenly disperse to obtain the self-adhesive gel.

[0014] Preferably, the mixing and dispersing temperature in step (1) and step (2) is room temperature.

[0015] The present invention also provides the use of the self-adhesive gel or the self-adhesive gel prepared by the above-mentioned preparation method in the preparation of scar repairing agents.

[0016] Furthermore, when the drug is administered, 1064nm laser irradiation is used to stimulate the photothermal properties of germanene and improve the efficacy. Preferably, the irradiation time is ≤5min.

[0017] Compared with the prior art, the present invention has the following beneficial effects:

[0018] The self-adhesive gel of the present invention is prepared from germanium, triamcinolone acetonide, polydimethylsiloxane, polyvinylpyrrolidone, water and ethanol, and can treat hypertrophic scars through photothermal, chemotherapy, hydration and self-adhesive effects, and can effectively overcome the shortcomings of current silicone gels, and has the following advantages:

[0019] 1) The usage time is greatly shortened, and you only need 45 days to get the ideal effect.

[0020] 2) The scar lightening effect is strong and the probability of recurrence is low.

[0021] 3) It has self-adhesive effect and does not require additional gauze or elastic bandage for fixation. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is a photothermal curve diagram of the gel of Example 1 of the present invention;

[0023] Figure 2 This is a photothermal response drug release curve of the gel of Example 1 of the present invention. DETAILED DESCRIPTION

[0024] In order to facilitate the understanding of the present invention, the present invention will be described more fully below with reference to the relevant drawings. The preferred embodiments of the present invention are given in the drawings. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive.

[0025] In the description of the present invention, unless otherwise clearly defined, terms such as heating, cleaning, weighing, freezing, etc. should be understood in a broad sense, and technicians in the relevant technical field can reasonably determine the specific meanings of the above terms in the present invention in combination with the specific content of the technical solution.

[0026] In the description of the present invention, the description with reference to the terms "some embodiments", "examples", etc. means that the specific methods and materials described in conjunction with the embodiments or examples are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific methods and materials described can be combined in any one or more embodiments or examples in a suitable manner.

[0027] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.

[0028] In the following examples and comparative examples, the experimental methods used are conventional methods unless otherwise specified, and the materials, reagents, etc. used are all commercially available unless otherwise specified.

[0029] Examples 1-4

[0030] The formula of each embodiment is shown in Table 1, and the specific preparation method is as follows:

[0031] (1) At room temperature, water, germanium, triamcinolone acetonide, and polyvinylpyrrolidone in a formula amount are mixed and dispersed uniformly to obtain a colloid;

[0032] (2) Adding the formulated amount of anhydrous ethanol and polydimethylsiloxane to the jelly obtained in step (1) at room temperature, and continuing to mix and disperse evenly to obtain a self-adhesive gel.

[0033] Table 1: Examples and Comparative Examples

[0034]

[0035] Comparative Example 1

[0036] The same as Example 1, the only difference is that the proportion of purified water is 10%, the proportion of anhydrous ethanol is 60%, and the other components and preparation method are the same as Example 1.

[0037] Comparative Example 2

[0038] The same as Example 1, the only difference is that the proportion of purified water is 60%, the proportion of anhydrous ethanol is 10%, and the other components and preparation method are the same as Example 1.

[0039] Comparative Example 3

[0040] The same as Example 1, the only difference is that the proportion of germanene is 0.5%, the proportion of water is 31.5%, and the other components and preparation method are the same as Example 1.

[0041] Comparative Example 4

[0042] The same as Example 1, the only difference is that the proportion of germanium ene is 4%, the proportion of water is 28%, and the other components and preparation method are the same as Example 1.

[0043] Comparative Example 5

[0044] The same as Example 1, the only difference is that the proportion of triamcinolone acetonide is 0.5%, the proportion of water is 32.5%, and the other components and preparation method are the same as Example 1.

[0045] Comparative Example 6

[0046] The same as Example 1, the only difference is that the proportion of triamcinolone acetonide is 7%, the proportion of water is 26%, and the other components and preparation method are the same as Example 1.

[0047] Comparative Example 7

[0048] The same as Example 1, the only difference is that the proportion of polyvinylpyrrolidone is 8%, the proportion of polydimethylsiloxane is 17%, and the other components and preparation method are the same as Example 1.

[0049] Comparative Example 8

[0050] The same as Example 1, the only difference is that the proportion of polyvinylpyrrolidone is 20%, the proportion of polydimethylsiloxane is 5%, and the other components and preparation method are the same as Example 1.

[0051] Performance testing and trial

[0052] 1. Gel photothermal performance test

[0053] 1.1. Photothermal performance test of gel

[0054] The gel prepared in Example 1 was evenly smeared on a glass slide in a circular shape with a thickness of about 2 mm and a diameter of about 2 cm, and dried naturally at room temperature to form a film. Then, it was irradiated with a 1064 nm laser for 5 minutes, and the temperature rise curve was observed and plotted.

[0055] The test results are detailed in Figure 1 .Depend on Figure 1 It can be seen that the prepared gel has the effect of self-heating in response to 1064nm laser, and the temperature rises rapidly by only 20°C in the first 2 minutes, and then tends to slow down. After being exposed to the laser for 5 minutes, the temperature rises by nearly 30°C. Considering tissue tolerance, etc., the laser irradiation time in subsequent experiments was set at 5 minutes.

[0056] 1.2 Photothermal responsive drug release ability of scar gel

[0057] The gel prepared in Example 1 was evenly smeared on a glass slide in a circular shape with a thickness of about 2 mm and a diameter of about 2 cm, and dried naturally at room temperature to form a film. Then the gel film and the glass slide were placed in a PBS solution with a pH of 7.4, and the film of the experimental group was irradiated with a 1064 nm laser for 5 minutes at the 5th and 15th hours, respectively, and the control group was not treated with laser, and the drug release curve of triamcinolone acetonide was detected and plotted by an ultraviolet spectrophotometer. The drug release curve was observed for 24 hours.

[0058] The experimental results are detailed in Figure 2 ,Depend on Figure 2 It can be seen that the gel of the present invention has the ability to release drugs in a photothermal response. Compared with the control group, the photothermal effect of the experimental group can increase the release rate of triamcinolone acetonide by about 80%.

[0059] 2. Evaluation of gel properties of examples and comparative examples

[0060] The samples of Examples 1-4 and Comparative Examples 1-8 were selected for performance testing and trial analysis. The performance comparison included evaluation of gel appearance, photothermal effect, film-forming time, and film-forming property; the trial effect evaluation included: treatment effect on the 45th day and recurrence on the 6th month. The overall test results are shown in Table 2. Table 3 gives a detailed table of the use effect evaluation.

[0061] The specific evaluation methods and standards are as follows:

[0062] 1. Performance testing

[0063] Gel appearance: Under normal lighting, a person with normal vision should visually inspect the gel's appearance. It should be a transparent gel with no visible foreign matter.

[0064] Photothermal effect: Apply the gel evenly on a glass slide in a circular shape with a thickness of about 2 mm and a diameter of about 2 cm, and dry it naturally at room temperature to form a film. Then irradiate it with a 1064nm laser for 5 minutes and detect the temperature change △T, which should be between 20℃ and 40℃.

[0065] Film-forming time: Apply the gel evenly on a glass slide in a circular shape with a thickness of about 2 mm and a diameter of about 2 cm, and dry it naturally at room temperature to form a film. The time for drying the film at room temperature should be no more than 1 hour.

[0066] Film-forming property: Apply the gel evenly on a glass slide in a circular shape with a thickness of about 2 mm and a diameter of about 2 cm, and dry it naturally at room temperature to form a film. After the film is formed, the film should be able to be completely peeled off from the glass slide.

[0067] Trial effectiveness: When trialed on subjects, the effectiveness should be no less than 80%.

[0068] 2. Evaluation of trial effect

[0069] 60 volunteers were recruited to try out the samples of the above-mentioned Examples 1-4 and Comparative Examples 1-8. The volunteers must have hypertrophic scars. The volunteers were randomly divided into 12 groups, with 5 people in each group. The scar gel prepared by Examples 1-4 and Comparative Examples 1-8 was used as the test product and acted on 12 groups of subjects respectively. Usage: Apply the scar gel evenly to the hypertrophic scar area of ​​the skin, wait for 2 hours, and irradiate evenly with a 1064nm laser for 5 minutes. The thin film formed by the scar gel can be removed after 8 hours. Apply once in the morning and evening every day for 45 days. Professional testers will score the volunteers to evaluate the treatment effect on the 45th day and the recurrence in the 6th month after stopping the treatment.

[0070] The efficacy indicators are defined as follows:

[0071] Effective: The treatment effect is effective on the 45th day, and there is no recurrence in the 6th month after stopping treatment, that is, the scar height (7-10 points), color (7-10 points), and texture (7-10 points) are consistent with normal skin (10 points);

[0072] Invalid: Other situations (1-6 points) are considered invalid.

[0073] Effectiveness = effective number of people / 5×100%.

[0074] Table 2. Evaluation results of gel properties of examples and comparative examples

[0075]

[0076]

[0077] Table 3 Detailed table of evaluation of trial effects of embodiments and comparative examples

[0078]

[0079]

[0080]

[0081] From the above evaluation results, it can be seen that germanium ene mainly affects the photothermal effect, thus affecting the efficacy. The photothermal temperature cannot be too low or too high. If it is too low, the efficacy is poor, and if it is too high, it will damage the normal tissues of the human body. The addition amount in the range of 1-3% has a better efficacy, and the laser irradiation time is better within 5 minutes. Triamcinolone acetonide has a direct impact on the effectiveness of scar gel. The addition amount is better at 1-5%. If the ratio is too low, the efficacy will be greatly reduced, and if the ratio is too high, there will be no substantial improvement.

[0082] As the main film-forming substances, the ratio of polyvinyl pyrrolidone and polydimethylsiloxane will affect the film-forming property. A too low ratio will cause the film to be easily damaged, and a too high ratio will cause no film to be formed. Preferably, the film-forming property is better in the range of polyvinyl pyrrolidone: polydimethylsiloxane = 0.8-3:1, and the best is 1.5:1. At the same time, the amount of solvent water and anhydrous ethanol added will affect the film-forming time and gel appearance of the scar gel. If the ratio is too low, it will cause the components to be unevenly dispersed in the solution and there will be foreign matter in the appearance; if the ratio is too high, it will lead to a long film-forming time. Preferably, polyvinyl pyrrolidone: water = 1: 1-4, polydimethylsiloxane: anhydrous ethanol = 1: 2-7, and the film-forming performance is better.

[0083] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0084] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A self-adhesive gel, characterized in that The raw materials include germanene, polydimethylsiloxane, polyvinylpyrrolidone, triamcinolone acetonide, anhydrous ethanol and water.

2. The self-adhesive gel according to claim 1, characterized in that According to weight percentage, it contains germanium: 1% to 3%, polyvinyl pyrrolidone: 10% to 20%, polydimethylsiloxane: 5% to 15%, triamcinolone acetonide: 1% to 5%, anhydrous ethanol: 30% to 50%, and water: 20% to 40%.

3. The self-adhesive gel according to claim 2, characterized in that According to the mass ratio, polyvinyl pyrrolidone: polydimethylsiloxane = 0.8-3:

1.

4. The self-adhesive gel according to claim 2, characterized in that According to the mass ratio, polyvinyl pyrrolidone: water = 1:1-4, polydimethylsiloxane: anhydrous ethanol = 1:2-7.

5. The self-adhesive gel according to claim 2, characterized in that According to weight percentage, the composition comprises 2% germanene, 15% polyvinyl pyrrolidone, 10% polydimethylsiloxane, 3% triamcinolone acetonide, 40% anhydrous ethanol and 30% purified water.

6. A method for preparing a self-adhesive gel according to any one of claims 1 to 5, characterized in that: The method comprises the following steps: (1) mixing and evenly dispersing a prescribed amount of water, germanium, triamcinolone acetonide and polyvinylpyrrolidone to obtain a jelly; (2) adding a prescribed amount of anhydrous ethanol and polydimethylsiloxane to the jelly obtained in step (1), and continuing to mix and evenly disperse to obtain the self-adhesive gel.

7. The preparation method according to claim 6, characterized in that: The mixing and dispersing temperature in step (1) and step (2) is room temperature.

8. Use of the self-adhesive gel according to any one of claims 1 to 5, or the self-adhesive gel prepared by the preparation method according to any one of claims 6 to 7 in the preparation of a scar repair agent.

9. The use according to claim 8, characterized in that When the medicine is administered, 1064nm laser irradiation is adopted.

10. The use according to claim 9, characterized in that The 1064nm laser irradiation time is ≤5min.

Citation Information

Patent Citations

  • Medical scar-repairing silicone gel dressing and preparation method thereof

    CN110302414A

  • Composite hydrogel as well as preparation method and application thereof

    CN113769088A

  • Gel of triamcinolone acetonide and econazole nitrate, its preparing and quality control method

    CN1813770A

  • Methods and compositions for modulating hair growth, wound healing and scar revision

    WO2012065065A1

Cited By

  • Self-adhesive gel as well as preparation method and application thereof

    CN121370732A